Genetic analysis of samples from wild populations opens new perspectives on hybridization between long‐tailed (Macaca fascicularis) and rhesus macaques (Macaca mulatta). Issue 12 (2nd November 2017) - Bunlungsup, Srichan; Kanthaswamy, Sree; Oldt, Robert F.; Smith, David Glenn; Houghton, Paul; Hamada, Yuzuru; Malaivijitnond, Suchinda
Abstract : In the past decade, many researchers have published papers about hybridization between long‐tailed and rhesus macaques. These previous works have proposed unidirectional gene flow with the Isthmus of Kra as the zoogeographical barrier of hybridization. However, these reports analyzed specimens of unknown origin and/or did not include specimens from Thailand, the center of the proposed area of hybridization. Collected specimens of long‐tailed and rhesus macaques representing all suspected hybridization areas were examined. Blood samples from four populations each of long‐tailed and rhesus macaques inhabiting Thailand, Myanmar, and Laos were collected and analyzed with conspecific references from China (for rhesus macaques) and multiple countries from Sundaic regions (for long‐tailed macaques). Ninety‐six single nucleotide polymorphism (SNP) markers specifically designed to interrogate admixture and ancestry were used in genotyping. We found genetic admixture maximized at the hybrid zone (15–20°N), as well as admixture signals of varying strength in both directions outside of the hybrid zone. These findings show that the Isthmus of Kra is not a barrier to gene flow from rhesus to long‐tailed populations. However, to precisely identify a southernmost barrier, if in fact a boundary rather than simple isolation by distance exists, the samples from peninsular Malaysia must be included in the analysis. Additionally, a long‐tailed to rhesus gene flow boundary was found between northern Thailand and Myanmar. Our results suggest that selection of long‐tailed and rhesus macaques, the two most commonly used non‐human primates for biomedical research, should take into account not only the species identification but also the origin of and genetic admixture within and between the species. Abstract : Hybridization between long‐tailed and rhesus macaques occurred beyond Isthmus of Kra.